Inhibition of Glyoxalase-I Leads to Reduced Proliferation, Migration and Colony Formation, and Enhanced Susceptibility to Sorafenib in Hepatocellular Carcinoma - Michel, Maurice; Hollenbach, Marcus; Pohl, Sabine; Ripoll, Cristina; Zipprich, Alexander (Frontiers in Oncology, 2019)
Background: Glyoxalase-I (Glo-I) is essential for detoxification of methylglyoxal (MGO), a byproduct of glycolysis. Overexpression of Glo-I has been linked to multi-drug resistance in cancer therapy. The aim of this study was to analyze Glo-I in hepatocellular carcinoma (HCC) and the effect of the multi-tyrosine kinase inhibitor sorafenib on Glo-I. Methods: Expression and specific activity of Glo-I was measured in human HCC samples, HCC-cell lines (HepG2, Huh7) and a hepatocyte cell line (AML 12). Cells were either treated with Glo-I inhibitors, ethyl pyruvate (EP, 1-20mM) and BrBzGSHCp2 (1-10µM), or sorafenib (2.5-10µM) and protein expression (Western Blot), proliferation (WST-assay), migration (scratch assay) and colony formation (clonogenic assay) were assessed. Results: High expression of Glo-I was detected in human HCC tissue samples. Huh7 showed highest expression and activity of Glo-I and revealed highest proliferation compared to AML 12 and HepG2. Targeting Glo-I by EP or BrBzGSHCp2 led to significantly reduced proliferation (20mM EP 24h: 57±12%), migration and colony formation. Glo-I inhibition by 20mM EP resulted in reduced expression of PDGFR-β (18±10%), VEGFR2 (46±11%), VEGF (61±10%), pERK/ERK (62±6%), NF-ĸB (44±12%) as well as stimulation of Nrf2 (243±36%). Similar results were seen with BrBzGSHCp2. Sorafenib treatment revealed elevation of Glo-I (10µM: 209±25%) and MGO. Co-treatment of EP and sorafenib led to an additional reduction of proliferation compared to sorafenib alone. Conclusion: Glo-I is positively correlated with HCC proliferation. Inhibition of Glo-I reduced proliferation, migration and colony formation. In turn, sorafenib increases Glo-I. Co-treatment using Glo-I inhibitors could enhance susceptibility of HCC to sorafenib.